Shakespeares värde och demokratins: Kritik och politik i Sverige och Norden, 1880–1960 - Sivefors, Per (Tidskrift för litteraturvetenskap, 2025)
The Values of Shakespeare and Democracy: Criticism and Politics in Sweden and the Nordic Countries, 1880–1960 This article examines how notions of Shakespeare’s literary value are related to aspects of democracy, especially in criticism on Shakespeare by Nordic scholars, but also in performance and fiction. It particularly suggests that such relations develop along two tracks. One of them is to emphasize the differences between Shakespeare’s time and the present, thus bringing out the anti- or pre-democratic nature of early modern society; the other is to see Shakespeare’s value as universal – which, in the context of the time, often means casting Shakespeare as a representative of democratic values, tolerance and freedom. These strategies take on particular contextual significance at a time when the Nordic countries became democracies in the modern sense of the term, and when subsequently, those democracies were perceived as threatened during the 1930s and 40s. Thus, whether or not criticism embraces Shakespeare’s universal value, its assumptions reflect a highly specific political and historical background.